Advanced corrosion-rate model for comprehensive seismic fragility assessment of chloride affected RC bridges located in the coastal region of india. (December 2021) - Dey, Abhijeet; Sil, Arjun
Abstract: In this study, a methodology is being proposed for performing seismic fragility analysis of corrosion affected bridges located in the coastal region of India. The study performed adopting this advanced corrosion rate model capturing nonlinearity that necessitates pitting corrosion as a realistic corrosion degradation mechanism rather than conventional uniform corrosion. With the application of advanced corrosion model, a distinct improvement over seismic fragility assessment achieved due to its capability to capture nonlinearity in the overall process of corrosion transport. The proposed model exhibits the corrosion rate accelerates after initial cracking of the concrete cover until at a phase, when severe cracking occurs leading to spalling of concrete. Based on the current degradation mechanism, the study estimates the capacity limit states of deteriorating reinforced concrete (RC) T-girder bridges as well as the impact of bridge degradation on the seismic response assessed using nonlinear time history analysis (NLTHA). However, the NLTHA of the finite element bridge models performed considering erraticism about material properties, geometries, ground motions and corrosion degradation parameters such that the uncertainties associated with the bridge population could be realistically taken into account as per the basic corrosion mechanism. Comparisons are drawn with respect to general and pitting corrosion as well as the adverse effect of pitting corrosion on the bridge service life has been identified. Thus, the output of the seismic fragility analysis would indicate some useful information in understanding the nonlinear crack growth of bridge vulnerability in marine environment, such that proper maintenance strategies could be framed for adequate safety of the highway infrastructure system for its enhanced design life.